Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/mnras/staa3324
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar radio emission mechanisms: a critique

Abstract: We consider critically the three most widely favored pulsar radio emission mechanisms: coherent curvature emission (CCE), beam-driven relativistic plasma emission (RPE) and anomalous Doppler emission (ADE). We assume that the pulsar plasma is one dimensional (1D), streaming outward with a bulk Lorentz factor γs ≫ 〈γ〉 − 1 ≳ 1, where 〈γ〉 is the intrinsic spread in the rest frame of the plasma. We argue that the formation of beams in a multi-cloud model is ineffective in the intrinsically relativistic case for pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 110 publications
1
55
0
Order By: Relevance
“…This constraint is a familiar one in the case of Langmuir waves; it implies a tension between rapid growth and curvature emission by Langmuir solitons above the plasma cutoff (e.g. Lakoba et al 2018;Melrose et al 2021a). The growth of trapped Alfvén waves is subject to a similar constraint: starting with a conservative growth criterion, we find that the peak of the curvature spectrum is ∼ 10 −2 of the cutoff frequency.…”
Section: General Constraints On Soliton Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This constraint is a familiar one in the case of Langmuir waves; it implies a tension between rapid growth and curvature emission by Langmuir solitons above the plasma cutoff (e.g. Lakoba et al 2018;Melrose et al 2021a). The growth of trapped Alfvén waves is subject to a similar constraint: starting with a conservative growth criterion, we find that the peak of the curvature spectrum is ∼ 10 −2 of the cutoff frequency.…”
Section: General Constraints On Soliton Formationmentioning
confidence: 99%
“…Very quickly a simple physical picture predicated on charge clumping in an electromagnetic cascade was developed, giving a transparent explanation for the observed linear polarization swings (Radhakrishnan & Cooke 1969;Ruderman & Sutherland 1975). But over five decades, no consensus has emerged on how the required charged soliton structures would develop; theorists have vigorously explored a variety of alternative emission mechanisms (see Melrose et al 2021a for a recent critical review). None of the alternatives have yielded a comparably compelling explanation for the linear polarization behavior that is observed in many, but not all, pulsars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As alternative mechanisms, relativistic plasma emission, anomalous Doppler emission, linear acceleration emission, and maser emission have been proposed. However, none of these theoretical methods are capable of fully explaining the pulsar emission mechanism (Melrose 1995;Melrose et al 2021). Therefore, single-pulse studies, including singlepulse-polarimetry, of pulsars with a variety of properties are crucial to fully understand pulsar emission physics (Rankin 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Their high brightness temperature makes astrophysicists believe that the radio pulse originates from the so-called coherent emission like the radio pulsar does, 1 , 2 although details for such collective radio emissions are still unclear. 3 , 4 Since the first discovery, 5 rapid progress has been made in the FRB field. Along with the increasing FRB number, it was found that some of them are individual events, i.e., do not repeat within a monitor period, while some sources are obviously repeating.…”
Section: Introductionmentioning
confidence: 99%